Etika dan Fungsi Media dalam Tayangan Televisi: Studi pada Program Acara Yuk Keep Smile di Trans Tv - Herawati, Erni (Bina Nusantara University, 2015)
Entertainment as media content in television has been critisized by society. Therefore, this research seeked out how media such as television runs its functions and ethics to society. The objective of this research is to find out the television functions and ethics. This research used qualitative approach and focused on analyzing the functions and ethics of television broadcast. Data were collected by observation and documentations review. The results are entertainment became the prime content of television but the functions have not been implemented responsibly yet to society. The ethics of how television produced and broadcasted the messages, especially the entertainment program, are the main problem. The economic factors become the main concern of the producer compared to the protection for special audiences such as children and teenagers.